Efficacy and safety of re-treatment with the same artemisinin-based combination treatment (ACT) compared with an alternative ACT and quinine plus clindamycin after failure of first-line recommended ACT (QUINACT): a bicentre, open-label, phase 3, randomised controlled trial - Hypolite Muhindo Mavoko, DrPhD; Carolyn Nabasumba, MD; Raquel Inocêncio da Luz, PhD; Halidou Tinto, PhD; Umberto D'Alessandro, ProfPhD; Andrew Kambugu, MD; Vito Baraka, MSc; Anna Rosanas-Urgell, PhD; Pascal Lutumba, ProfPhD; Jean-Pierre Van geertruyden, PhD (Elsevier, 2017)
Summary: Background: Quinine or alternative artemisinin-based combination treatment (ACT) is the recommended rescue treatment for uncomplicated malaria. However, patients are often re-treated with the same ACT though it is unclear whether this is the most suitable approach. We assessed the efficacy and safety of re-treating malaria patients with uncomplicated failures with the same ACT used for the primary episode, compared with other rescue treatments. Methods: This was a bicentre, open-label, randomised, three-arm phase 3 trial done in Lisungi health centre in DR Congo, and Kazo health centre in Uganda in 2012-14. Children aged 12-60 months with recurrent malaria infection after treatment with the first-line ACT were randomly assigned to either re-treatment with the same first-line ACT, an alternative ACT, which were given for 3 days, or quinine-clindamycin (QnC), which was given for 5-7 days, following a 2:2:1 ratio. Randomisation was done by computer-generated randomisation list in a block design by country. The three treatment groups were assumed to have equivalent efficacy above 90%. Both the research team and parents or guardians were aware of treatment allocation. The primary outcome was the proportion of patients with an adequate clinical and parasitological response (ACPR) at day 28, in the per-protocol population. This trial was registered under the numbers NCT01374581 in ClinicalTrials.gov and PACTR201203000351114 in the Pan African Clinical Trials Registry. Findings: From May 22, 2012, to Jan 31, 2014, 571 children were included in the trial. 240 children were randomly assigned to the re-treatment ACT group, 233 to the alternative ACT group, and 98 to the QnC group. 500 children were assessed for the primary outcome. 71 others were not included because they did not complete the follow-up or PCR genotyping result was not conclusive. The ACPR response was similar in the three groups: 91·4% (95% CI 87·5-95·2) for the re-treatment ACT, 91·3% (95% CI 87·4-95·1) for the alternative ACT, and 89·5% (95% CI 83·0-96·0) for QnC. The estimates for rates of malaria recrudescence in the three treatment groups were similar (log-rank test: χ2=0·22, p=0·894). Artemether-lumefantrine was better tolerated than QnC (p=0·0005) and artesunate-amodiaquine (p<0·0001) in the modified intention-to-treat analysis. No serious adverse events were observed. The most common adverse events reported in the re-treatment ACT group were anorexia (31 [13%] of 240 patients), asthenia (20 [8%]), coughing (16 [7%]), abnormal behaviour (13 [5%]), and diarrhoea (12 [5%]). Anorexia (13 [6%] of 233 patients) was the most frequently reported adverse event in the alternative ACT group. The most commonly reported adverse events in the QnC group were anorexia (12 [12%] of 98 patients), abnormal behaviour (6 [6%]), asthenia (6 [6%]), and pruritus (5 [5%]). Interpretation: Re-treatment with the same ACT shows similar efficacy as recommended rescue treatments and could be considered for rescue treatment for Plasmodium falciparum malaria. However, the effect of this approach on the selection of resistant strains should be monitored to ensure that re-treatment with the same ACT does not contribute to P falciparum resistance. Funding: Fonds Wetenschappelijk Onderzoek, Vlaamse Interuniversitaire Raad-Universitaire Ontwikkelings Samenwerking, European and Developing Countries Clinical Trials Partnership, and the Belgian Technical Cooperation-Programme d'Etudes et d'Expertises-in the Democratic Republic of Congo.